Identifying Drug Therapy Problems Through Patient Consultation at Community Pharmacies: A Quality Improvement Project. Issue 1 (March 2020) - Patel, Mira; Campbell, Michael; Moslem, Mobeen; Spriggel, Preston; Warholak, Terri
Abstract : Objective: This study aimed to identify drug therapy problems during patient counseling at prescription pickup in the community pharmacy setting. Methods: This descriptive quality improvement project assessed the number of drug therapy problems identified during patient consultation. Data were collected for 2 months at 6 community pharmacies in Arizona. The criterion for inclusion was any patient new or transferred prescription consultation provided by a pharmacist or pharmacy intern. Three doctor of pharmacy candidates collected data on a standardized form. The percentage and type of drug therapy problems identified during patient consultation were calculated. Results: Data collectors counseled patients on 1305 prescriptions, and of those, 29 drug therapy problems (2.2%) were identified after the pharmacists' final check. The most common problems involved patient drug allergy or sensitivity (20.7%). Conclusions: This project suggests that drug therapy problems in a community pharmacy setting can be identified via patient counseling at the time of prescription pickup.